2023
DOI: 10.3390/polym15061518
|View full text |Cite
|
Sign up to set email alerts
|

A New Optimization Strategy of Highly Branched Poly(β-Amino Ester) for Enhanced Gene Delivery: Removal of Small Molecular Weight Components

Abstract: Highly branched poly(β-amino ester) (HPAE) has become one of the most promising non-viral gene delivery vector candidates. When compared to other gene delivery vectors, HPAE has a broad molecular weight distribution (MWD). Despite significant efforts to optimize HPAE targeting enhanced gene delivery, the effect of different molecular weight (MW) components on transfection has rarely been studied. In this work, a new structural optimization strategy was proposed targeting enhanced HPAE gene transfection. A seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Polymers were synthesized via RAFT polymerization, which offers versatility in synthesizing macromolecules with narrow dispersity in molecular weight and a large monomer base. , For the present study and to better measure the effectiveness of a single polymer chemical composition, low dispersity polymers were desired. This was targeted to better evaluate the effectiveness of a single polymer chemical composition; formulations with large dispersity in molecular weight have been found to cause significant and unpredictable changes in transfection efficiency. , Polymer composition was determined via NMR, with a cationic incorporation of 43–52% being achieved. Molecular weight and dispersity were evaluated via aqueous SEC, with all polymers having Đ < 1.3.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Polymers were synthesized via RAFT polymerization, which offers versatility in synthesizing macromolecules with narrow dispersity in molecular weight and a large monomer base. , For the present study and to better measure the effectiveness of a single polymer chemical composition, low dispersity polymers were desired. This was targeted to better evaluate the effectiveness of a single polymer chemical composition; formulations with large dispersity in molecular weight have been found to cause significant and unpredictable changes in transfection efficiency. , Polymer composition was determined via NMR, with a cationic incorporation of 43–52% being achieved. Molecular weight and dispersity were evaluated via aqueous SEC, with all polymers having Đ < 1.3.…”
Section: Resultsmentioning
confidence: 99%
“…This was targeted to better evaluate the effectiveness of a single polymer chemical composition; formulations with large dispersity in molecular weight have been found to cause significant and unpredictable changes in transfection efficiency. 60,61 Polymer composition was determined via NMR, with a cationic incorporation of 43− 52% being achieved. Molecular weight and dispersity were evaluated via aqueous SEC, with all polymers having Đ < 1.3.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…It was found that the branched structure significantly enhanced the transfection efficiency compared to the corresponding linear PAE (LPAE) and commercial transfection reagents. Additionally, different optimization strategies, for example, molecular designs (e.g., distribution precipitation) and a precise synthesis (e.g., the addition of cell-penetrating peptides), were applied to efficient PAE development. So far, thousands of PAE vectors have been synthesized and developed for clinical applications. ,, However, their transfection performance is still not comparable to that of viral vectors. ,, The gene delivery behavior of polymer vectors is closely related to their chemical structure, thus, to pursue the aim of improving the gene delivery performance of PAEs, the structural properties of PAEs have been continuously studied and optimized. While, through the studies during the past few decades, all the common structural factors of PAEs (e.g., chemical composition, molecular weight (MW) and topology etc.)…”
mentioning
confidence: 99%
“…Additionally, different optimization strategies, for example, molecular designs (e.g., distribution precipitation) and a precise synthesis (e.g., the addition of cell-penetrating peptides), were applied to efficient PAE development. 14 16 So far, thousands of PAE vectors have been synthesized and developed for clinical applications. 5 , 17 , 18 However, their transfection performance is still not comparable to that of viral vectors.…”
mentioning
confidence: 99%